The Concept of Cultural Imagery : Imagologi with and not against the Early Voelkerpsychologie - Dukić, Davor (2009)
Cultural imagery, as the central concept of image studies, may be defined as a set of characteristic imagemes of a particular culture in a particular period. J. Leerssen defines the “ imageme” as a set of images (typically contradictory in value) of a particular, usually ethnic or national, entity. Thus, cultural imagery is an ideal construct, which does not reside in any single individual consciousness ; however each instance of individual imagery is received with relation to the cultural imagery, and is included therein. The bearer of particular cultural imagery is a particular culture, or a collective constructed according to an integration criterion: the supranational, national, ethnic, denominational, social, gender, ideological, etc. The paper will discuss the issue of (re)constructing particular cultural imagery: applying qualitative and/or quantitative methods, the importance of fictional and non-fictional, canonized and popular texts ; the relationship between cultural imagery and the value system of a culture ; dealing with the cultural imagery of hybrid and border cultures ; the issue of describing changes in cultural imagery. The concept of cultural imagery will be of value in analyzing and describing the complex structure of autoimages and heteroimages of a culture, thus overcoming the binary nature of classical imagology based on analyzing discrete imagemes (e.g., the image of Germans in French literature vs. the image of the French in German literature). These general issues will be illustrated with examples, primarily from South Slavic cultures of the Early Modern Age and the 19th century